Human-Related Microsporidian Spores in Farm Chickens from Makeni, Sierra Leone - Umar Anjum; Sergio Llorens-Berzosa; Raoul E. Guetiya Wadoum; Fernando Izquierdo; María de los Ángeles Peña; Ethel Ukaegbu; Antonio Peña-Fernández (Biology and Life Sciences Forum, 2025)
The aim of this paper is to study the presence and temporal variation/distribution of microsporidian species (Enterocytozoon bieneusi and Encephalitozoon spp.) in chickens from different farms in Bombali district (Sierra Leone). Fresh faecal samples were collected from twenty chickens in April 2019, while twelve were collected in Summer 2022. Six faecal samples gave positive results microscopically (spores of Encephalitozoon spp. were observed in five samples, and E. bieneusi in one). Five samples from 2019 were found to be positive by molecular methods: two E. intestinalis and E. hellem, and one E. bieneusi; meanwhile, ten samples from 2022 were positive for spores of the genus Encephalitozoon, specifically from eight chicken.